Healing The Human Person ―― Post-Traumatic Counselling: Healing of Wounds caused by Violence - Kaberia, Isaac K. (My University, 2018)
The healing of wounds caused by violence provides a space for recovery from emotional and psychological harm caused to victims and offenders. Trauma is an experience of both victims and offenders. Meeting such needs creates an environment conducive to the reconciliation process. The discussion of post-traumatic counselling as the process of healing the wounds is addressed from both the restorative and reconciliation perspectives. Involvement of victims, offenders and community members in a quest to identify needs and responsibilities promotes healing among the parties involved.
Keywords: Post-traumatic counselling; Victim-offender conferencing; Family group conferencing; Community conferencing; Howard Zehr